Pengaruh Utang Luar Negeri, Al-Sharf, dan Ekspor terhadap Cadangan Devisa Negara Indonesia - Asraaf Efendi Batubara; Marliyah Marliyah; Khairina Tambunan (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Foreign exchange reserves are used to see how far a country can conduct international trade and to show the strength and weakness of a country's economic fundamentals. Factors that affect foreign exchange reserves are foreign debt, exports, imports, the rupiah exchange rate, and the inflation rate. These factors will bring many advantages and benefits in increasing the country's foreign exchange reserves. But there are still some that do not affect the country's foreign exchange reserves. The purpose of this study was to determine the effect of foreign debt, Al-Sharf and exports on the country's foreign exchange reserves. This type of research is quantitative research. The data source used is secondary data obtained from the Central Statistics Agency (BPS) and Bank Indonesia. The analysis technique used in this study is multiple linear regression analysis using the SPSS 26 program. The results of the study state that the variables of foreign debt and Al-Sharf have a significant effect on the country's foreign exchange reserves. Meanwhile, the export variable does not have a significant effect on the country's foreign exchange reserves. Keywords: Foreign Debt,Al-Sharf, Exports, and State Reserves